New Approaches to Targeting B Cells for Myasthenia Gravis Therapy - Huda, Ruksana (Frontiers in Immunology, 2020)
Current therapies for myasthenia gravis (MG) are limited, and many investigations have recently focused on target-specific therapies. B cell-targeting monoclonal antibody (mAb) therapies for MG are increasingly attractive due to their specificity and efficacy. The targeted B cell biomarkers are mainly the cluster of differentiation (CD) proteins that mediate maturation, differentiation, or survival of pathogenic B cells. Additional B cell-directed therapies include non-specific peptide inhibitors that preferentially target specific B cell subsets. The primary goals of such therapies are to intercept autoantibodies and prevent the generation of an inflammatory response that contributes to the pathogenesis of MG. Treatment of patients with MG using B cell-directed mAbs, antibody fragments, or selective inhibitors have exhibited moderate to high efficacy in early studies, and some of these therapies appear to be highly promising for further drug development. Numerous other biologics targeting various B cell surface molecules have been approved for the treatment of other conditions or are either in clinical trials or preclinical development stages. These approaches remain to be tested in patients with MG or animal models of the disease. This review article provides an overview of B cell-targeted treatments for MG, including those already available and those still in preclinical and clinical development. We also discuss the potential benefits as well as the shortcomings of these approaches to development of new therapies for MG and future directions in the field.